Quo Vadis Machine Learning-Based Systems Condition Prognosis?—A Perspective - Mohamed Benbouzid; Berghout, Tarek (Electronics, 2023)
Data-driven prognostics and health management (PHM) is key to increasing the productivity of industrial processes through accurate maintenance planning. The increasing complexity of the systems themselves, in addition to cyber-physical connectivity, has brought too many challenges for the discipline. As a result, data complexity challenges have been pushed back to include more decentralized learning challenges. In this context, this perspective paper describes these challenges and provides future directions based on a relevant state-of-the-art review.